The Effect of Semantic Ambiguity on Second Language Learners' Comprehension - Diana Dian Sari Tampubolon; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This paper aims to examine the effect of semantic ambiguity on reading comprehension in second language (L2) learners. The type of research used is a literature study with a qualitative descriptive approach, which refers to various relevant sources that discuss lexical and structural ambiguity in the process of learning English as a foreign language. The findings in this study explain that semantic ambiguity significantly hinders reading comprehension, especially when learners encounter unfamiliar vocabulary or sentence structures with multiple meanings. Lexical ambiguity tends to be more difficult than structural ambiguity due to limited vocabulary acquisition and students' tendency to understand literal meaning. In addition, the lack of contextualized reading strategies exacerbates misunderstandings. Therefore, lessons that emphasize the practice of identifying and interpreting ambiguity, as well as strengthening inferential skills, are essential for improving reading comprehension ability in second language learning.